Perga's electrical characteristics - Regrut Tomáš; Hlaváčová Zuzana; Novák Ján; Božiková Monika; Hlaváč Peter; Brindza Ján; Cviklovič Vladimír; Ardonová Veronika (Journal on Processing and Energy in Agriculture, 2017)
The aim of this study was to measure the electrical properties of perga. We measured the capacitance, resistance and impedance. Each property was measured at all frequencies three times. Average value and standard deviation has been computed from these ones. The resistance, impedance, and capacitance decreases with frequency according to power function. The impedance has a slightly higher value as resistance, which is caused by the capacitance of perga. It was determined that the dielectric constant of perga increases when the moisture content of perga increases. The minimal decrease is at higher frequencies. The measurements indicate that perga must be included in the organic heterogeneous multi-component dielectrics or semi-conductors.